2017
DOI: 10.1016/j.addbeh.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Baseline health status and quality of life after alcohol treatment for women with alcohol dependence

Abstract: Background Research suggests that women with alcohol use disorders (AUDs) experience more severe medical and social consequences from alcohol use compared to men, but little is known about health improvements following alcohol treatment. Methods This study sought to characterize the pre-treatment health status of 138 alcohol dependent women enrolled in 12 sessions of female-specific group or individual outpatient treatment and examine the degree to which alcohol treatment might promote positive quality of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
1
16
0
1
Order By: Relevance
“…A number of RCTs have yielded newly available, evidence-based female-specific treatment protocols for AUD and SUD treatment that are at least equivalent in positive outcomes to evidence-based control treatments. 59 , 60 , 62 , 70 , 74 , 79 Outcomes for secondary (non-AUD) patient problems, such as depression and anxiety, 59 , 60 trauma symptoms, 69 cardiovascular function, 98 health behaviors, drug use, and quality of life 99 , 100 from these female-specific treatments also have been positive. NIAAA’s focus on implementation studies in conjunction with the study of mechanisms of change 101 should accelerate testing the incorporation of female-specific interventions into community settings—not just addiction specialty clinics but also primary care and general mental health settings.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…A number of RCTs have yielded newly available, evidence-based female-specific treatment protocols for AUD and SUD treatment that are at least equivalent in positive outcomes to evidence-based control treatments. 59 , 60 , 62 , 70 , 74 , 79 Outcomes for secondary (non-AUD) patient problems, such as depression and anxiety, 59 , 60 trauma symptoms, 69 cardiovascular function, 98 health behaviors, drug use, and quality of life 99 , 100 from these female-specific treatments also have been positive. NIAAA’s focus on implementation studies in conjunction with the study of mechanisms of change 101 should accelerate testing the incorporation of female-specific interventions into community settings—not just addiction specialty clinics but also primary care and general mental health settings.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Epstein & B.S. McCrady, [5] showed how a significant improvement in the quality of life has been observed after alcohol treatment, but this is related to alcohol dependence rather than alcohol consumption in general. J.…”
Section: Introductionmentioning
confidence: 99%
“…In a prior study (Epstein et al, in press) we reported comparable, positive outcomes for a 12-session, individual modality female-specific cognitive behavioral therapy (FS-CBT) protocol tested against a gender-neutral individual CBT condition (Epstein & McCrady, 2009) for women with AUD. During treatment, women in both conditions were highly engaged, satisfied with treatment, reduced their drinking, depression, anxiety, tobacco and other drug use, and improved their interpersonal functioning, self-efficacy, coping skills, and motivation (Bold, Epstein, & McCrady, 2017; Epstein et al, in press). Positive changes were maintained for the 12 months following treatment.…”
Section: Introductionmentioning
confidence: 99%